How Japan’s Cultural Norms Affect Policing: A Side-By-Side Comparison with the United States - Tran, Katrina (2017)
The ways of policing have been critiqued throughout the years—some have advocated for a direct approach while others value diplomatic techniques. Consideration is emphasized by how culture affects policing in the United States and Japan. In the United States, the customs of policing involve violence, individualism, pragmatism, social mobility, and low power distance, whereas Japan encourages non-violence, face-saving, conservatism, and high power distance. The difference in these cultural norms reflects how policing is conducted in these two countries. To understand how policing in these two countries are different, this paper examines the difference of cultural norms and its impact on both police and community